Factors Affecting the Decision to Work at Ampera 2 Tak Restaurant Branch Veteran Bintaro, South Jakarta - Asmaniati, Fetty; Amrullah, Amrullah (Technium Social Sciences Journal, 2023)
The purpose of this study is to evaluate the impact of employee age, wages, and work discipline on the decision to work at Ampera 2 Tak Cabang Veteran Bintaro Restaurant. This research is a quantitative descriptive study with multiple analysis methods using SPSS software. The population and sample in this study consisted of 32 employees at Ampera 2 Tak Cabang Veteran Bintaro Restaurant, with a saturated sampling technique used. Data were collected using a questionnaire using the Likert scale with a range of values from 1 to 5. The results of the study showed that employee age, wages, and work discipline have a significant impact on the decision to work. Employee age has a significant impact on the decision to work because the majority of employees at Ampera 2 Tak Cabang Veteran Bintaro Restaurant are young and productive, thus they have high creativity in completing their tasks and have a high sense of responsibility towards assigned tasks. Wages also have a significant impact on the decision to work because the wages given by Ampera 2 Tak Cabang Veteran Bintaro Restaurant can meet the financial needs of employees. Work discipline also has a significant impact on the decision to work, because employees who are disciplined in carrying out their tasks can use their time and energy more effectively to complete their assigned tasks.